Multiple vehicles co-operative routing in Singapore - Chee, Yi Xu (2016)
Traffic congestion has become a big issue for civil engineers as the number of vehicles increases rapidly every year. In this project, the problem of routing multiple vehicles in an urban area was taken into consideration. This project aims to explore ways to reduce traffic congestion in traffic control authority’s perspective and to reduce travel time in road user’s perspective. The explorations were done by simulating Singapore map in Simulation of Urban MObility (SUMO). Advanced Interactive Microscopic Simulator for Urban and non-urban Network (AIMSUN) was also used to have quick test of some cases in smaller scale. I had attempted to implement an ERP-like system. That is, to introduce weight (price) to roads that are likely to have traffic congestion. If the weight of a road is high, the probability of choosing that road is low. Iterative simulation model has been used to optimize the weights. The weights for every roads in the first iteration is the length of the road. For every subsequent iteration, methodologies were developed to adjust the weights for every iteration. Methodologies were developed for weight adjustment. In the first methodology, the weight of a road is increased if it’s average speed during simulation is slower than 50% of the maximum speed allowed in that road. Second methodology is basically same as the first methodology, but this time the weight is decreased if a road’s average speed during simulation is faster than 50% of the maximum speed allowed. In the second methodology, some weights may get negative value if associating roads keep having high average speed. The third methodology is a fix for that. Forth methodology is a fix to oscillation effect that might occur. In conclusion, after a number of iterations, the overall network performance did improve. However, while many road users got reduction in travel time, many other road users were sacrificed. This is due to the fact that weight adjustment formulas doesn’t take individual travel time into consideration.